Exploring the Future of Development Learning: The Open Learning Campus. - Jagannathan, Sheila (International Journal of Advanced Corporate Learning (iJAC), 2017)
The Open Learning Campus is changing the landscape for development learning around the world. By incorporating innovative ways of sharing knowledge across development professionals, partners, and clients, OLC provides learners a real opportunity to seamlessly and efficiently learn and grow, thereby increasing motivation and retention. This study explores the Open Learning Campus, its knowledge sharing tools and systems, as well as its impact within and outside the World Bank Group.